Knowledge, Attitudes, and Ordering Patterns for Routine HIV Screening among Resident Physicians at an Urban Medical Center. (July 2016) - Bares, Sara; Steinbeck, Jennifer; Bence, Lauren; Kordik, Abbe; Acree, Mary Ellen; Jih, Jane; Farnan, Jeanne; Watson, Sydeaka; Rasinski, Kenneth; Schneider, John; Pitrak, David
Background: We sought to measure resident physician knowledge of HIV epidemiology and screening guidelines, attitudes toward testing, testing practices, and barriers and facilitators to routine testing. Methods: Resident physicians in internal medicine, pediatrics, obstetrics and gynecology, and emergency medicine were surveyed. Results: Overall response rate was 63% (162 of 259). Half knew details of the HIV screening guidelines, but few follow these recommendations. Less than one-third reported always or usually performing routine testing. A significant proportion reported only sometimes or never screening patients with risk factors. This was despite a strong belief that HIV screening improves patient care and public health. The most common barriers to testing were competing priorities and forgetting to order the test. Elimination of written consent and electronic reminders was identified as facilitators to routine testing. Although an institutional policy assigns responsibility for test notification and linkage of HIV-positive patients to care to the HIV care program, only 29% were aware of this. Conclusions: Few resident physicians routinely screen for HIV infection and some don't test patients with risk factors. While competing priorities remain a significant barrier, elimination of written consent form and electronic reminders has facilitated testing. Increasing the awareness of policies regarding test notification and linkage to care may improve screening.